The experience of implementing an interprofessional research methods course for student health professionals of population health and clinical practice. Getting the right fit - Wilson, A. (Journal of University Teaching and Learning Practice, 2008)
Purpose: This paper reports on the adaptation of an existing interpretive and critical research methods course in nursing for postgraduate student health professionals in a School of Population Health and Clinical Practice. Methods: A cyclical approach of inquiry, reflection and planning was undertaken by the teaching team to make changes to the existing course for implementation for the current and following academic year. Critical reflections from two student evaluations during the course contributed to the re-design. Main Findings: Two main findings emerged: (1) cross-disciplinary teaching teams can work successfully if there is true collaboration of stakeholders; and (2) it is feasible to conduct an effective interdisciplinary qualitative research methods course for student health professionals. Conclusions: Interdisciplinary research methods courses need to be structured so that students interact with each other to enhance their knowledge of other disciplines and value learning about other professional viewpoints and issues.